2017
DOI: 10.17860/mersinefd.305760
|View full text |Cite
|
Sign up to set email alerts
|

Siber Zorbalık Üzerine Ülkeler Arası bir Karşılaştırma: İtalya ve Türkiye Örnekleri

Abstract: The present study aimed to investigate how Italian and Turkish university students perceive cyber bullying. A total of 256 Italian (161 females, 95 males) and 122 Turkish (76 females, 44 males, 2 did not report gender) university students were recruited by convenience sampling. The ages of the participants ranged between 18 and 33 for both the Italian sample (M = 20.9; SD = 1.92) and the Turkish sample (M = 22.77; SD = 2.47). Data were collected via a questionnaire which included two vignettes depicting differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 21 publications
(41 reference statements)
0
1
0
Order By: Relevance
“…Bullying victimization is a phenomenon that results in negative consequences for the population of countries with diverse cultures such as Brazil (e.g., Krieger & Mendes, 2012), Canada (e.g., Salmon et al, 2018), Nigeria (e.g., Fenny & Falola, 2020); Korea (e.g., Moon et al, 2011); Japan and the United States (e.g., Hilton et al, 2010). However, based on previous evidence, it is known that the culture of a particular country may influence, for example, the understanding of bullying, the prevalence of bullying, the methods of bullying or the family’s characteristics of the victim (e.g., Hilton et al, 2010; Hosozawa et al, 2021; Mura et al, 2017). For instance, Hilton et al (2010) revealed that adolescents from United States tended to exhibit higher levels of verbal bullying, in contrast to Japanese adolescents, where indirect bullying was more prevalent.…”
Section: Introductionmentioning
confidence: 99%
“…Bullying victimization is a phenomenon that results in negative consequences for the population of countries with diverse cultures such as Brazil (e.g., Krieger & Mendes, 2012), Canada (e.g., Salmon et al, 2018), Nigeria (e.g., Fenny & Falola, 2020); Korea (e.g., Moon et al, 2011); Japan and the United States (e.g., Hilton et al, 2010). However, based on previous evidence, it is known that the culture of a particular country may influence, for example, the understanding of bullying, the prevalence of bullying, the methods of bullying or the family’s characteristics of the victim (e.g., Hilton et al, 2010; Hosozawa et al, 2021; Mura et al, 2017). For instance, Hilton et al (2010) revealed that adolescents from United States tended to exhibit higher levels of verbal bullying, in contrast to Japanese adolescents, where indirect bullying was more prevalent.…”
Section: Introductionmentioning
confidence: 99%